The secret keeper of Jaipur [large type] - Joshi, Alka (Thorndike Press large print core, 2021)
"In New York Times bestselling author Alka Joshi's intriguing new novel, henna artist Lakshmi arranges for her protégé, Malik, to intern at the Jaipur Palace in this tale rich in character, atmosphere, and lavish storytelling. It's the spring of 1969, and Lakshmi, now married to Dr. Jay Kumar, directs the Healing Garden in Shimla. Malik has finished his private school education. At twenty, he has just met a young woman named Nimmi when he leaves to apprentice at the Facilities Office of the Jaipur Royal Palace. Their latest project: a state-of-the-art cinema. Malik soon finds that not much has changed as he navigates the Pink City of his childhood. Power and money still move seamlessly among the wealthy class, and favors flow from Jaipur's Royal Palace, but only if certain secrets remain buried. When the cinema's balcony tragically collapses on opening night, blame is placed where it is convenient. But Malik suspects something far darker and sets out to uncover the truth. As a former street child, he always knew to keep his own counsel; it's a lesson that will serve him as he untangles a web of lies"--